IDENTIFIKASI JENIS-JENIS MOLUSCA DAN ARTOPHODA DI EKOSISTEM ESTUARIA GAMPONG JAWA KECAMATAN KUTA RAJA BANDA ACEH SEBAGAI MODUL AJAR ZOOLOGI - Rafsanjani, Aiza; Ibrahim, Ibrahim; Samsuar, Samsuar; Zubainur, Cut Morina (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to identify the types of Molluscs and Arthropods in the estuary ecosystem of Gampong Jawa, Kuta Raja District, Banda Aceh, and to develop the results of the study as a Zoology teaching module. Sampling was carried out from 22 to 28 May 2013, with two repetitions and an observation interval of twice a day. The method used was a line transect with a purposive sampling technique, using three line transects and three observation plots. Data analysis used the Shannon-Wiener diversity index, Simpson dominance index, Pielou evenness index, and density formula. The results showed that there were 768 individuals divided into 26 species. The diversity index (H') of Molluscs and Arthropods ranged from 2.55-2.61, dominance index 0.072-0.451, evenness index 1.042-1.094. The level of diversity of Molluscs and Arthropods in the area is relatively high. Based on the research results, a Zoology teaching module was developed that integrates knowledge about the diversity of Molluscs and Arthropods in the local estuarine ecosystem. This module is designed to improve students' understanding of local biodiversity and the importance of estuarine ecosystem conservation. In conclusion, the Gampong Jawa estuarine ecosystem has a high diversity of Molluscs and Arthropods, and the results of this study can be used as a contextual learning resource in teaching Zoology.